Next-Generation Sequencing in a Cohort of Asian Indian Patients with the Duchenne Muscular Dystrophy Phenotype: Diagnostic Yield and Mutation Spectrum - Nerakh, Gayatri; Ranganath, Prajnya; Murugan, Sakthivel (Journal of Pediatric Genetics, 2020)
Multiplex ligation-dependent probe amplification (MLPA) detects exonic deletions and duplications in the DMD gene in around 65 to 70% of patients with the Duchenne muscular dystrophy (DMD) phenotype. This study looks at the diagnostic yield of next-generation sequencing (NGS) and the mutation spectrum in an Asian Indian cohort of MLPA-negative cases with the DMD phenotype. NGS-based sequencing of DMD gene was done in 28 MLPA-negative cases (25 male probands with the DMD phenotype and 3 obligate carrier mothers of deceased affected male patients) and disease-causing variants were identified in 19 (67.9%) of these cases. Further molecular testing in four of the remaining nine cases revealed gene variants associated with limb girdle muscular dystrophies. Thus, NGS-based multigene panel testing for muscular dystrophy-associated genes or clinical exome sequencing rather than targeted DMD gene sequencing appears to be a more cost-effective testing modality with better diagnostic yield, for MLPA-negative patients with the DMD phenotype.
Keywords: Duchenne muscular dystrophy; next-generation sequencing; DMD gene sequence variants